Studies on Fusarium wilt Disease of Cucumber - Majdah M.Y. Al-Tuwaijri (Journal of Applied Pharmaceutical Science, 2015)
Eight isolates of Fusarium oxysporum f. sp. cucumerinum; the causal organism of Fusarium wilt of cucumber plants; were isolated from wilted cucumber plant samples collected from eight different localities in Egypt . These isolates were pathogenic to the susceptible cucumber cultivar “Biet alpha”. Isolate 3 was the most virulent, followed by isolate 4 , while the least pathogenic was isolate 5. Potato Dextrose medium was the best medium for linear and amount of growth for all tested isolates, whereas rate of growth varied between the different tested isolates with the different tested media. Optimum temperature for the fungal linear growth was 27°C, followed by 28°C, while the best amount of growth was obtained at 25°C for all tested isolates. Cucumber genotypes were susceptible to Fusarium oxysporum f.sp. cucumerinum and differed significantly in their susceptibility. The most tolerant cucumber genotype was “Zeina” as well as it recorded the highest survival plants. DNA analysis detected 33 loci with an average 4.125 loci/isolate. The highest number of polymorphic loci was 6 loci in both Fus 1&4 isolates, while the lowest was 1 loci in Fus 6 only. UPGMA cluster analysis divide into two sub clusters, one of them included Fus 6 only and the second include the rest seven isolates with different similarity values. 100 & 614 bp were detected in both highly pathogenic isolates and it could be carrying the genetic information affecting pathogenicity of Fusarium to cucumber plants. Grouping of Trichoderma isolates in UPGMA cluster analysis and variation in DNA profiles among isolates was not related to their biocontrol ability. Biocontrol agents great affected Fusarium growth in dual cultures and reduced it under laboratory conditions. Biocontrol agents minimized the disease parameters in comparing with infested control treatments by the most aggressive isolate under greenhouse condition.
Keywords: Cucumber,pathogenicity,Fusarium,biocontrol,Trichoderma.